Validating the wheelchair outcome measure for residents in long-term care. (May 2014) - Parvaneh, Shahriar; Mortenson, William B.; Miller, William C.
Abstract Purpose: To determine the retest reliability and construct validity of the self-report and proxy versions of the wheelchair outcome measure (WhOM) among residents in long-term care. Method: The WhOM was administered to 55 wheelchair users living in residential care (38 self-respondents and 17 proxy respondents). Retest data were collected to estimate reliability using intraclass correlation coefficients (ICCs) for each of the tool scores (Importance, Satisfaction and Importance × Satisfaction). For construct validity testing, Spearman's correlation coefficients were used to assess whether WhOM scores were correlated with scores from the Late Life Function and Disability Instrument (LLDI) and Geriatric Depression Scale (GDS). Results: The ICCs for the WhOM scores were between 0.68 and 0.84. Moderate correlations were found between the self-respondents and proxy respondents groups with Importance × Satisfaction and LLDI (r = 0.46–0.50). No other significant correlations were found. Conclusions: This study provides evidence for the reliability and validity of the WhOM for adults in residential care, but further testing is warranted to ensure it can facilitate prescription of the right device at the right time for residents in these settings. Implications for Rehabilitation Clients who reside in long-term care (LTC) institutions represent a population who have unique needs because of the varied types of activities in which they participate. This study provides support for use of the WhOM on an individual basis among self-responding residents. The study provides some support and use of the WhOM with groups of residents who require proxy respondents. Additional studies with a larger sample size are needed to further explore the psychometrics of the measure.